FUNGSI FISIK MANGROVE SEBAGAI PENAHAN ABRASI DI PESISIR KOTA MEDAN PROVINSI SUMATERA UTARA (Physical Function of Mangrove as Retaining Abrasion at the Coastal of Medan, North Sumatra) - Josephin Saut Sintong Panjaitan; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2015)
This research aims to determine the physical environmental or socio - economic of local community gives more dominant influence to damage the mangrove forest, changes of shoreline has been occurred from 2003 – 2014, changes of shoreline due to the influence of erosion at coastal of Medan and the dominant species of mangrove as retaining abrasion at coastal of Medan. Changes of Shoreline can be seen with the overlay method. This research uses field observation and interview to the local community directly. The results of research shows that socio - economic of local community gives more dominant influence than physical environmental to damage the mangrove forest. changes of shoreline has been occurred from 2003 – 2014 is about 57 meter. Based on field observation, many mangrove forest are converted into farm and many illegal logging has been occurred in the location of research.Keywords : Physical Function, Mangrove, Abrasion, Overlay, Shoreline